KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN ORONG SELATAN, DESA GEGERUNG, KECAMATAN LINGSAR, KABUPATEN LOMBOK BARAT - Fathul Muin; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Gegerung is one of the villages in the Lingsar District, West Lombok Regency. The research was conducted using the observation method. Based on the study, it was found that the yard plants in South Orong Hamlet, Gegerung Village, Lingsar District, West Lombok Regency have an H’= 2.25, which indicates moderate diversity, moderate distribution, and moderate community stability.